TECHNICAL FEASIBILITY FOR THE DEVELOPMENT OF COMPETENCIES UNDER THE COPC STANDARDS IN THE TELECOMMUNICATIONS SECTOR - William A. Niebles; Leonardo D. Niebles; Author (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The main objective of this project is to full fill the required needs of telecommunications organizations in Colombia. The methodology type used is a descriptive field, transactional, not experimental. The results show that the creation of a method is required to create technical competencies under the COPC standards, which induces to improve processes, favoring changes in the execution of processes, to raise the levels of efficiency and effectiveness in the accomplishment of them.